Gaya Bahasa Kiasan pada Cerita Fabel dalam Buku Teks Bahasa Indonesia SMP Kelas 7 Terbitan Kemendikbud - Dini Artini; Agus Triani; Labbaika Ashayidatina; Pertiwi Anggraini; Muhammad Mukhlis (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This research is entitled "Style of Figurative Language in Fable Stories in Indonesian Language Textbooks for 7th Grade Middle School Published by the Ministry of Education and Culture". The purpose of this study is to provide information and knowledge about the language styles in the textbook. By using a qualitative approach with a descriptive method. The source of the data in this research is a collection of fable stories that are in the Indonesian language textbook for Class 7 Middle School. The data collection technique uses the documentation technique. In data acquisition, the researcher started by reading, marking, taking notes, and grouping. The results of the research conducted on "figurative language styles in fable stories in Indonesian language textbooks for 7th grade junior high schools published by the Ministry of Education and Culture" contained 10 data which were divided into 7 language styles. The seven language styles are: 1 hyperbole language style, 1 personification style, 1 metominia style, 3 hypalase style, 1 antonymous language style, 2 sarcasm language style, and 1 satire language style.